Helietta apiculata: a tropical weapon against Chagas disease. Issue 22 (17th November 2019) - Elena Ferreira, Maria; Rojas de Arias, Antonieta; Yaluff, Gloria; Vera de Bilbao, Ninfa; Nakayama, Hector; Torres, Susana; Schinini, Alicia; Torres, Susana; Serna, Elva; Torrecilhas, Ana Claudia; Fournet, Alain; Cebrián-Torrejón, Gerardo
Abstract: The present study pretends to evaluate the in vivo efficacy of the crude chloroform bark extract of Helietta apiculata, then the activity will be compared with the reference drug, benznidazole, in acute Trypanosoma cruzi infected mice when administered by oral route. The chloroformic extract of Helieta apiculata was administered by oral route at 5, 10 and 50 mg/kg daily for two weeks. This study has shown a moderate efficacy of the H. apiculata bark extract in reducing T. cruzi parasitaemia in 42 to 54% after a monitoring of 60 days post-infection and when compared with control groups. Concerning mice mortality, only two only two mice died, one from the control group and the other one from the group threated with 10 mg of the chlorofom extract of H. apiculata, suggesting the potential of H. apiculta extracts as a safe and inexpensive treatment of Chagas disease. Abstract :